Comportamento dos acadêmicos, docentes e técnicosadministrativos da clínica odontológica da Unioeste: riscos ocupacionais e atividades desenvolvidas = Behavior of university students, faculty and administrative technicians at the Unioeste dental clinic: occupational risks and performed activities - Neide Tiemi Murofuse; Débora Cristina Ignácio Alves; Gleicy Cristina Fávero; Aline de Oliveira Brotto (Universidade Estadual de Maringá, 2008)
Os profissionais, usuários e demais envolvidos no atendimento odontológico estão expostos a diversos riscos ocupacionais. A pesquisa teve como objetivos conhecer as atividadesdesenvolvidas na clínica odontológica; identificar os riscos existentes e os equipamentos de proteção individual utilizados; averiguar a ocorrência de acidentes; e identificar os treinamentosrecebidos e as sugestões para prevenir acidentes. A amostra do tipo não probabilística foi composta por 61 acadêmicos, 27 docentes e 12 técnicos-administrativos. Os dados foram coletados por meio de observação dos atendimentos realizados e de um questionário semiestruturado. Das 28 observações realizadas, a maioria foi na Clínica Integrada do Adulto (53,6%), seguida pela Clínica Integrada Infantil (35,7%) e pela Dentística (10,7%). Existem riscos para atotalidade dos docentes e técnicos, sendo referidos o biológico e o de acidente. A maioria (98,4%) dos acadêmicos considera a existência de riscos, contudo 1,6% a negam e 8,2% deles sofreramacidentes. Quanto ao uso de Equipamentos de Proteção Individual (EPI), 25% dos técnicosadministrativos não têm o hábito de usá-los. Embora os acadêmicos e docentes tenham relatado seu uso como forma de proteção, nem todos citaram a paramentação completa. Assim, o registrode acidentes e a baixa adesão aos EPI's evidenciou a necessidade de treinamento e conscientização dos envolvidos. Professionals, users and other people involved in dental treatment services are exposed to several kinds of occupational risks. The objective of this research was to learn about the activities developed at the dental clinic; identify the existence of occupational risks and the individual protection equipment used;investigate the occurrence of accidents; and indentify the training received and the suggestions for accident prevention. The non-probabilistic sample was composed of 61 university students, 27faculty and 12 administrative technicians. Data collection was carried out in two stages: the observation of the treatments performed and a semi-structured questionnaire. Most of the 28observations were conducted at the Integrated Clinic for Adults (53.6%), followed by observations at the Integrated Clinic for Children (35.7%) and at the Dental Section (10.7%). According to all the professors and technicians, there are risks in the activities performed, with biological and accident risks as the most cited by the subjects. The majority (98.4%) of university students consider theexistence of risks, 1.6% of them deny it, and 8.2% of them have already suffered an accident. Concerning the use of Individual Protection Equipment (EPI), 25% of the administrativetechnicians do not regularly use them. Although the university students and faculty mentioned the use of the equipment as a form of protection, not all of them mentioned all the items to be worn.Thus, the record of accidents and the rare use of the Individual Protection Equipments showed the need for training and raising awareness in the people involved in the treatment services.